Di-n-butyl phthalate disrupts neuron maturation in primary rat embryo neurons and male C57BL/6 mice. Issue 2 (17th January 2022) - Lee, Seulah; Lee, Wonjong; Yang, Seonguk; Suh, Yeon Ji; Hong, Dong Geun; Chang, Seung-Cheol; Kim, Hyung Sik; Lee, Jaewon
ABSTRACT: Di- n -butyl phthalate (DBP) is commonly used as a plasticizer and its usage continues to increase in conjunction with plastic consumption. DBP is readily released into air, drinking water, and soil, and unfortunately, is a potent endocrine disrupter that impairs central nervous system functions. Previously DBP was found to (1) arrest the cell cycle of C17.2 neural progenitor cells (NPCs) at the G1 phase, (2) reduce numbers of newly generated neural stem cells in the mouse hippocampus, and (3) adversely affect learning and memory. Other investigators also noted DBP-mediated neurotoxic effects, but as yet, no study has addressed the adverse effects of DBP on neuronal differentiation. Data demonstrated that at 200 μM DBP induced apoptosis in rat embryo primary neurons by increasing reactive oxygen species levels and inducing mitochondrial dysfunction. However, no significant effect was detected on neurons at concentrations of ≤100 μM. In contrast, doublecortin/microtubule associated protein-2 (DCX/MAP2) immunocytochemistry showed that DBP at 100 μM delayed neuronal maturation by increasing protein levels of DCX (an immature neuronal marker), without markedly affecting cell viability. Further in vivo studies confirmed that DCX + cell numbers were significantly elevated in the hippocampus of DBP-treated mice, indicating that DBP delayed neuronal maturation, which is known to be associated with impaired memory retention. Data demonstrated that DBP might disrupt neuronal maturation, which is correlated with reduced neurocognitive functions.